Successful rehabilitation and release of two severely injured Formosan black bears (Ursus thibetanus formosanus) with desensitization to routine treatment procedures - Ai-Mei Chang; Chen-Chih Chen; Yun-Chieh Tuan; Lee-Shuan Lin (BMC Veterinary Research)
Abstract Background Wildlife rehabilitation is crucial for the recovery of injured endangered species; however, this process can induce significant stress, potentially leading to secondary injuries and complications. This case report details the rehabilitation of two severely injured Formosan black bears (Ursus thibetanus formosanus) with desensitization techniques as an alternative approach to reducing stress while promoting voluntary cooperation during treatment. Case presentation Patient 1 was an adult female bear with injuries, including the loss of the second, third and fourth phalanges of the left forelimb and extensive necrosis of the right palm. Patient 2 was a subadult male suffering from multiple gunshot wounds, severe necrosis of the distal part of the right wrist, and a fracture of the right mandibular ramus and left humerus. Both bears underwent desensitization training, which fostered calmness during routine procedures and facilitated smooth recovery throughout rehabilitation. Pre-release training focused on rebuilding physical capacity and developing natural behaviors, as well as human avoidance, to increase survival and reduce human-bear conflicts. Conclusions The successful outcomes, characterized by complete recovery and avoidance of human interactions, underscore the effectiveness of desensitization strategies in wildlife rehabilitation. This approach not only enhances the quality of medical care but also mitigates the risks of post-release conflicts, contributing to the conservation of endangered species.